2004
DOI: 10.1161/01.cir.0000121426.43044.2b
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone, Through Novel Signaling Proteins, Is a Fundamental Molecular Bridge Between the Genetic Defect and the Cardiac Phenotype of Hypertrophic Cardiomyopathy

Abstract: Background-Human hypertrophic cardiomyopathy (HCM), the most common cause of sudden cardiac death in the young, is characterized by cardiac hypertrophy, myocyte disarray, and interstitial fibrosis. The genetic basis of HCM is largely known; however, the molecular mediators of cardiac phenotypes are unknown. Methods and Results-We show myocardial aldosterone and aldosterone synthase mRNA levels were elevated by 4-to 6-fold in humans with HCM, whereas cAMP levels were normal. Aldosterone provoked expression of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(194 citation statements)
references
References 54 publications
6
185
3
Order By: Relevance
“…Indeed, pressure-overloaded LIMP-2 KO mice show abnormal IDs on electron microscopy and their N-cadherin distribution is disturbed, suggesting a defect in the adherens junctions. The strength of adherens junctions is determined by the binding affi nity between N-cadherin and β-catenin (22), which is regulated by phosphorylation of the latter (19,20). We show in vivo as well as in vitro that loss of LIMP-2 disturbs this N-cadherin-β-catenin complex.…”
Section: Mechanisms Of Limp-2-mediated Response To Loadingmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, pressure-overloaded LIMP-2 KO mice show abnormal IDs on electron microscopy and their N-cadherin distribution is disturbed, suggesting a defect in the adherens junctions. The strength of adherens junctions is determined by the binding affi nity between N-cadherin and β-catenin (22), which is regulated by phosphorylation of the latter (19,20). We show in vivo as well as in vitro that loss of LIMP-2 disturbs this N-cadherin-β-catenin complex.…”
Section: Mechanisms Of Limp-2-mediated Response To Loadingmentioning
confidence: 84%
“…The functional integrity of the ID depends on the proper interaction between P(Ser37)-β-catenin and cadherin (19,20). Therefore, we investigated whether the absence of LIMP-2 aff ected the binding of P-β-catenin to cadherin.…”
Section: Limp-2 Regulates Id Integritymentioning
confidence: 99%
“…PKD is activated by PMA and PE in a Bis I-sensitive manner in NRVMs (16). Aldosterone also activates PKD in cardiomyocytes in culture and in mice (46). Furthermore, Gö6976 inhibits fetal gene expression in cardiomyocytes activated by aldosterone.…”
Section: Discussionmentioning
confidence: 97%
“…Sato and Funder 72 demonstrated PKC-dependent, aldosterone-induced hypertrophy in neonatal myocytes that was enhanced by elevated serum glucose and opposed by corticosterone. More recent studies have shown that cardiac hypertrophic markers (eg, natriuretic peptide precursor type A and B) and ␣-actin 1 are clearly increased in rat cardiac myocytes in response to aldosterone and involve phosphorylation of protein kinase D. 75 A number of other intracellular signaling pathways can also be upregulated by aldosterone, including PI3-kinase-p100␦, which promotes expression of the collagen genes COL1A1, COL1A2, and COL3A1, transforming growth factor-␤1 (TGF-␤1) in rat cardiac fibroblasts (a known profibrotic factor), connective tissue growth factor, 76 and plasminogen activator inhibitor. 77 Regulation of these pathways often has several levels of complexity; for example, upregulation of connective tissue growth factor is mediated by MR activation, the p38 MAPK pathway, and interactions between the 2.…”
Section: Fuller and Youngmentioning
confidence: 99%
“…Studies in the cardiac troponin T-Q92 transgenic mouse model of human hypertrophic cardiomyopathy (HCM) suggest that aldosterone is a major link between sarcomeric mutations and cardiac phenotype in HCM and, if confirmed in additional models, signals the need for clinical studies to determine the potential beneficial effects of MR blockade in human HCM. 75 Whether or not aldosterone acts directly on cardiac fibroblasts is unclear, with some investigators showing direct anabolic effects (collagen production), 80 whereas others have not. 81 Recently, Pratt et al suggested that aldosterone can promote proliferation of cardiac fibroblasts by activating specific cellular signaling cascades such as k-Ras and the MAPK1/2 cascade.…”
Section: Fuller and Youngmentioning
confidence: 99%